Clinical Outcomes of the Double Lateral Sliding Bridge Flap Technique with Simultaneous Connective Tissue Graft in Sextant V Recessions: Three-Year Follow-Up Study - Norberto Quispe-López; Antonio Castaño-Séiquer; Beatriz Pardal-Peláez; Pablo Garrido-Martínez; Cristina Gómez-Polo; Jesús Mena-Álvarez; Javier Montero-Martín (Applied Sciences, 2022)
The presence of isolated or multiple gingival recessions in the mandibular anterior region is a challenge for the clinician, as they may be associated with a shallow vestibule, high frenum insertion and/or little or no attached gingiva. Only limited evidence is available on the use of the double lateral sliding bridge flap technique with connective tissue graft (CTG) technique for treating gingival recessions in the mandibular anterior region. The aim of this study was to describe and evaluate the clinical and esthetic outcomes of the double lateral sliding bridge flap technique with CTG on isolated and multiple gingival recessions at the level of the mandibular incisors. Nine patients required treatment of gingival recessions in the mandibular incisors at the University of Salamanca (Spain) (seven females, two males; mean age: 27.9 ± 6.9) with a total of 14 isolated (42.9%) and multiple (57.1%) Miller class II and III gingival recessions. After a mean follow-up of 36 months, the mean percentage of root coverage was 80.5% for all treated recessions. Statistically significant differences (p < 0.05), were observed for reduction in recession depth, increased width of keratinized tissue and increased gingival thickness, this being dependent on the Miller class. The esthetic outcome was acceptable, with a final mean esthetic score of 7.4 out of 10. The double lateral sliding bridge flap surgical technique with CTG is an effective procedure for the coverage of isolated and multiple gingival recessions in the anterior mandibular region, as it offers satisfactory esthetic results.